The rise of E-Sports and potential for Post-COVID continued growth - Kim, Young Hoon; Nauright, John; Suveatwatanakul, Chokechai (Sport in society, 2020)
E-sports is an event involving professional game competitions. Despite a significant growth of e-sports industry, research findings and literature, including systematic evaluation and comparison of destinations are still in infant stage. Thus, the current paper attempts to review e-sports industry and address the multiple indicators for success. The results of this study show that the economic impact by esports is significant for a destination. In particular, government strategic plans and investment should be considered for strategic development of e-sports particularly in the wake of the COVID-19 pandemic.